From the Forest to the Port: Vereenigde Javasche Houthandel Maatschappij In Semarang, 1917-1942 - Dwi Mahdiyah; Putri Agus Wijayati (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study discusses the history of the establishment and operational dynamics of Vereenigde Javasche Houthandel Maatschappij (Vejahoma), a timber company located in Semarang from 1917 to 1942. The increasing demand for processed wood was a factor in the formation of this company. The main branch office was in Semarang, as a trading center and its proximity to teak-producing areas, such as Blora and Rembang. This study uses historical methods, which include heuristics, verification, interpretation, and historiography by utilizing primary sources such as colonial newspapers namely De Locomotief, De Koerier, and company documents from the ZBW Leibniz Informationszentrum Wirtschaft and Delpher. The results of the study show that Vejahoma underwent a transformation from a mere distributor of raw wood to a timber industry company producing various processed wood. The company implemented an adaptive marketing strategies, participated in exhibitions, and was active in colonial socio-economic organizations. Despite fluctuations, Vejahoma managed to survive through contracts with the government and product diversification. This research reveals the important role of Vejahoma in the global timber trade network during the colonial period.